Effect of Process Variables on Cr (IV) Removal from Liquid Waste Using Guava Leaf (Psidium guava) - . Mariana; . Hisbullah; Komala Pontas; Ferry Soraya; Purwana Satriyo (Syiah Kuala University, 2012)
The removal of Cr(IV) in aqueous solution by Guava Leaf (Psidium Guajava) as a bio-sorbent was experimentally investigated. The experiment was carried out in a batch stirred reactor at room temperature. The effects of certain parameters, such as concentration of bio-sorbent and contact time, were investigated. The removal increased with contact time and concentration of bio-sorbent. The results showed that the contact time is directly proportional to the sorption capacity and the sorption efficiency. The sorption efficiency of Cr (VI) was highest at 5 grams bio-sorbent, while the sorption capacity of Cr (VI) was highest in bio-sorbent 1 gram under current experimental condition. The optimum removal of Cr (VI) using guava leaves occurred while stirring 30 minutes.